Analisis Efisiensi Material dan Estimasi Biaya Berdasarkan Perbandingan Volume dan Berat Material Struktur - Mifidyah Putri Palilati; Ilyas Ichsan; Sartan Nento; Ratna Dwi Ma’sum; Rayfaldi Suqrafid Buhongo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The use of materials in short-span and long-span building structures, particularly in the use of formwork, concrete, and steel, is expected to reduce the volume of materials required for the structure. Changing the span design has the potential to provide cost efficiencies and overall structural safety. This research was conducted at the Mufida shopping center on Jend. Sudirman No. 22, Limba U1, South Kota, Gorontalo. Based on the analysis, the material requirements for each element, such as beams, columns, floor slabs, and footings, were calculated. This research focused on comparing the volume and weight of materials required for the two designs. The results of the material requirements study indicate that changes in span result in variations in the volume of concrete, reinforcing steel, and formwork. The two-span design requires more structural elements such as beams and columns, but the structure's dimensions tend to be smaller, achieving material volume efficiency. The total material cost calculation for the two-span design proved to be approximately 27.64% more efficient than the long-span design. Factors influencing this cost efficiency include the volume and type of materials, the implementation method, and the more even load distribution in the alternative design.